Sterile syringe access conditions and variations in HIV risk among drug injectors in three cities - Bluthenthal, Ricky N.; Malik, Mohammed Rehan; Grau, Lauretta E.; Singer, Merrill; Marshall, Patricia; Heimer, Robert (Addiction (Abingdon, England), 2004)
ABSTRACT Aim  Better sterile syringe access should be associated with a lower likelihood of syringe re‐use and receptive syringe sharing, although few empirical studies have examined gradients in syringe access using both individual and ecological data. In this study, we compare syringe re‐use and receptive syringe sharing among injection drug users (IDUs) with syringe exchange program (SEP) and legal over‐the‐counter pharmacy access with limits on syringes that can be purchased, exchanged or possessed to IDUs with no pharmacy sales but unlimited syringe access through SEPs. We address three questions: (1) Does residing in an area with no legal syringe possession increase the likelihood of police contact related to possessing drug paraphernalia? (2) Among direct SEP users, is use of more permissive SEPs associated with less likelihood of syringe re‐use and receptive syringe sharing? (3) Among non‐SEP users, is residing in an area with pharmacy access associated with lower likelihood of syringe re‐use and receptive syringe sharing? Design  Quantitative survey of IDUs recruited from SEPs, subject nomination and outreach methods. Multivariate analyses compared police contact, syringe re‐use and receptive syringe sharing among IDUs recruited in three cities. Findings  In multivariate analyses, we found that police contact was associated independently with residing in the area with no legal possession of syringes; among SEP users, those with access to SEPs without limits had lower syringe re‐use but not lower syringe sharing; and that among non‐SEP users, no significant differences in injection risk were observed among IDUs with and without pharmacy access to syringes. Conclusion  We found that greater legal access to syringes, if accompanied by limits on the number of syringes that can be exchanged, purchased and possessed, may not have the intended impacts on injection‐related infectious disease risk among IDUs.